Thrift Hunter: Mengapa Membeli Baju Second-hand? - Leni Susanti; Muhammad Fithrayudi Triatmaja (Universitas Muhammadiyah Sorong, 2023)
Trends in fashion change very quickly and make many people vying to get the latest fashion items from various brands. Developments in the fast fashion industry and ever-changing trends make 80 million clothes produced every year. This leads to an increase in the amount of fashion waste. One of the efforts to reduce the accumulation of fashion waste at this time is the existence of thrift shop that provides used clothes that are still worth using and sold at low prices but the quality provided is the same as new clothes. Procurement of used clothes or used clothes or second-hand clothes is through imports. However, the import of used clothes is prohibited in Indonesia. Anything that is forbidden is haram in Islam. This study examines the motivation of consumers in making purchasing decisions based on uniqueness, environmental consciousness and religiosity. The method used is quantitative. SmartPLS 24 was used as an analysis tool. The sample in this study is young people who buy used clothes as many as 100 respondents. The results of this study indicate that religiosity does not have a significant influence on purchasing decisions. Environmental consciousness and uniqueness have been shown to have a significant influence on purchasing decisions. Of the three latent variables presented, it is known that the environmental consciousness variable was the most influential factor in purchasing decisions made by second-hand clothing buyers.